2012
DOI: 10.1111/j.1460-9568.2012.08198.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range temporal correlations in the subthalamic nucleus of patients with Parkinson’s disease

Abstract: Neuronal activity in the subthalamic nucleus (STN) of patients with Parkinson's disease (PD) is characterised by excessive neuronal synchronization, particularly in the beta frequency range. However, less is known about the temporal dynamics of neuronal oscillations in PD. In this respect long-range temporal correlations (LRTC) are of special interest as they quantify the neuronal dynamics on different timescales and have been shown to be relevant for optimal information processing in the brain. While the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 94 publications
2
51
0
Order By: Relevance
“…For the analysis of connectivity, the bipolar channels were grouped into pairs, with three channel pairs for the connections in each STN (left STN: L01-12, L12-23, and L01-23; right STN: R01-12, R12-23, and R01-23). Notably, in comparison to other studies of connectivity involving STN (e.g., Klostermann et al, 2007;de Solages et al, 2010;Hirschmann et al, 2011;Litvak et al, 2011) an advantage of the present study is that we used an anatomical reconstruction of the electrode trajectory (Scho¨necker et al, 2009) for analyzing only those bipolar channels with at least one contact in STN (see Hohlefeld et al, 2012, for details and for the justification of including contact pairs in the analysis). The present selection approach ensures that if in a given bipolar channel (e.g., channel 23) both contacts were outside of STN (for channel 23 this would mean that the dorsal end of the electrode track being out of STN), then this channel was excluded and no coherence was calculated between this channel and others.…”
Section: Data Recordingsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the analysis of connectivity, the bipolar channels were grouped into pairs, with three channel pairs for the connections in each STN (left STN: L01-12, L12-23, and L01-23; right STN: R01-12, R12-23, and R01-23). Notably, in comparison to other studies of connectivity involving STN (e.g., Klostermann et al, 2007;de Solages et al, 2010;Hirschmann et al, 2011;Litvak et al, 2011) an advantage of the present study is that we used an anatomical reconstruction of the electrode trajectory (Scho¨necker et al, 2009) for analyzing only those bipolar channels with at least one contact in STN (see Hohlefeld et al, 2012, for details and for the justification of including contact pairs in the analysis). The present selection approach ensures that if in a given bipolar channel (e.g., channel 23) both contacts were outside of STN (for channel 23 this would mean that the dorsal end of the electrode track being out of STN), then this channel was excluded and no coherence was calculated between this channel and others.…”
Section: Data Recordingsmentioning
confidence: 99%
“…Ten patients (six males; mean age 61 years, range 47-71 years) diagnosed with idiopathic PD (mean disease duration 10 years, range 5-20 years) participated in the study, as described in our previous study (Hohlefeld et al, 2012), where further details about the patients were reported (see Table 1 therein). This data set was reanalyzed for the purposes of the present study.…”
Section: Experimental Procedures Patients and Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Invasive recordings in nonhuman primates, however, have reported 1/f spectra for the amplitude modulation in both low and high gamma bands [53]. Recordings from the subthalamic nucleus in Parkinson patients even show prominent LRTC in the very high-frequency gamma range (>200 Hz), especially when treated with the dopamine-precursor drug Levodopa [54].…”
Section: Insights From the Application Of Dfa To Neuronal Oscillationsmentioning
confidence: 99%